Vanishing Contagion Spreads - Duarte, Diogo; Prieto, Rodolfo; Rindisbacher, Marcel; Saporito, Yuri F. (Management Science, 2022)
We study default in a multifirm equilibrium setting with incomplete information. Defaults are consistent with the firm’s balance sheet and aggregation. We show that the endogenous volatility and jump size of debt and equity generated by other firms’ shocks vanish as the number of firms in the economy increases. As a result, credit spreads depend asymptotically only on the firms’ own cash flow risk. Our vanishing contagion spread result calls into question recent findings based on production economies, in which quantities of risk (volatilities and jump sizes of securities) are specified exogenously, that attribute credit spreads mostly to contagion. This paper was accepted by Kay Giesecke, finance.